Information Seeking Behavior in an Electronic Environment: A Review - Puttaswamy, R. M.; Krishnamurthy, M. (Journal of Information and Knowledge, 2014)
The advancement of Information and Communication Technology (ICT) in recent era has made the information services available to the users on their desktop as well as on their laptop and hand held e-book reader. This trend has made the way for tremendous growth of e-resources which is considered as one of the most powerful tools for the global communication and exchange of information. This has made the users to depend on e-resources for their teaching and research activities. The study aimed at finding the information seeking behavior of users in an electronic environment. This paper summarizes the results of thirty six user studies previously conducted in the electronic environment.